Dampak Pelaksanaan Program Pendidikan Gizi terhadap Produktivitas dan Kesehatan Pekerja - Saputra, Rizki Iwari (STIKES Yayasan RS.Dr.Soetomo, 2025)
Workforce productivity is one of the key indicators driving a country's economic growth. Several companies in Indonesia have reported issues related to workers’ nutrition and productivity. One example is PT XYZ Indonesia, which in 2024 reported that 73% of its employees were classified as overweight or had obesity grade 1, while 30% had elevated blood glucose levels. This study aims to analyze the impact of a nutrition education program on workers’ health indicators. An experimental design with an intervention approach was employed to evaluate the effectiveness of the nutrition education program as a strategy to improve worker productivity and health. The intervention was carried out over a period of eight weeks. The study population comprised employees of PT XYZ Indonesia, and a purposive sampling method was used to select 100 participants, divided evenly into intervention and control groups. The paired t-test results showed a significant increase in nutrition knowledge scores among the intervention group after completing the program (p < 0.05). A positive correlation was observed, indicating that improved nutritional understanding was closely associated with increased work productivity. A regression coefficient value of 0.56 (p = 0.003) further indicated that workers in the intervention group had higher health status scores compared to those in the control group.